Investigating the Possible Threats from Vegetal Cover Removal and Open Dumpsite to Groundwater Quality - Kwawuvi, D.; Ewemoje, T. A.; Owofadeju, F. K.; Adesina, A. F. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
This study investigated the possible groundwater quality threats from excessive removal of vegetation due to urban growth in an open dumpsite in Waterloo, Brong Ahafo Region, Ghana. 15 water samples were collected from five (5) functional Hand-dug wells at increasing distance from the dumpsite. The samples were assessed for some physico-chemical parameters. Descriptive statistics were applied to investigate the quality of groundwater samples from the Hand-dug wells. The groundwater was slightly acidic. Total Suspended Solids (TSS) and Total Coliform count were high for the groundwater samples but total dissolved solids (TDS) were within the permissible limits of Ghana Ministry of Water Resources (GMWR) and WHO. Analysed parameters such as Ca2+, Na+, Cl- and Cu conformed to the prescribed limits of GMWR and WHO for drinking water while Pb was above the permissible limits of both. Fe2+ conformed to the limit by GMWR but was above WHO. Cd was above the permissible limit of GMWR but fell within that of WHO. Urban growth effects investigated through the use of Landsat images of 1986, 2000, 2006 and 2011 with the aid of ArcGIS 10.5 and ENVI 4.7 revealed that the study area, within these years, drastically reduced in forest cover due to the increase in built-up and has the tendency to cause contamination to groundwater in the area.